Characterization of tapioca starch plasticized by 1-ethyl-3-methylimidazolium acetate - Ismail, S. (Penerbit UTM Press, 2017)
Starch is one of natural materials that been used for producing biodegradable materials. The starch-based materials are produced through a process known as gelatinization with the presence of plasticizer and elevated temperature. Properties of starch-based materials are lacking in terms of viscosity, water absorption, thermal and mechanical properties compare with synthetic materials. Researchers are involved in finding ways for improvement of starch-based materials properties and one of that is introducing new plasticizer. 1-ethyl-3-methylimidazolium acetate, EmimOAc is an ionic liquid that used as plasticizer to produce thermoplastic starch. Starch plasticized by EmimOAc were prepared with different total plasticizer contents (50%,70%) and EmimOAc/water ratio (1:6,1:4,2:3 wt%). The thermoplastic starches were characterized in terms of morphology, crystalline structure and thermal degradation. The results showed that 70% of total plasticizer contents were mixed well during gelatinization process. EmimOAc contributed to granule disruption as shown by SEM. Based on the XRD analysis, it was shown that thermoplastic starch at 70% total plasticizer contents and 1:4 wt% ratio of EmimOAc/water, caused disruption of the A-type crystalline structure, generated VH-type crystalline structure and thus increased the mobility of the amorphous starch. The presence of EmimOAc promotes the thermal degradation of starch molecules as described by TGA. Therefore, plasticizer contents and EmimOAc/water ratio are vital parameters that influences the properties of thermoplastic starch. © 2017 Penerbit UTM Press. All rights reserved.